Isolation of Endophytic Fungus from Leaves of Uncaria cordata (Lour.) Merr and Antibacterial Activity Against Propionibacterium acnes and Escherichia coli - Melzi Octaviani; Winda Yusma Ameliah; Neni Frimayanti; Meiriza Djohari; Haiyul Fadhli (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Uncaria cordata (Lour). Merr (akar kaik-kaik) is one of the medicinal plants used as antibacterial because it contains bioactive compounds that can inhibit the growth of microorganisms. The plant is one of the sources of endophyte fungal isolates that can be developed as an alternative to producing antibacterial compounds. This research aimed to isolate the endophytic fungus from the leaves of U. cordata and know the antibacterial activity against Propionibacterium acnes and Escherichia coli by disc diffusion. The Fungi that were isolated from the leaves of U. cordata were 17 isolates. The isolates were continued for antibacterial activity testing: IFED 1 (Nigrospora sp.), IFED 2 (Aspergillus sp.), IFED 3 (Fusarium sp.), and IFED 4, whose genus was unknown. The results obtained were fungal isolates IFED 1 to IFED 4 had activity in inhibiting the growth of P. acnes with moderate category (18.16 mm) and weak categories (6.21, 6.16, and 6.68 mm) and in E. coli with moderate category (14.56 mm) and weak categories (6.53, 6.71, and 7.23 mm). The results of One-Way ANOVA and Tukey's test showed a significant difference (p <0.05) between the diameter of the inhibition zone with the type of endophytic fungus supernatant isolated from the leaves of U. cordata. The best isolate of endophytic fungi inhibiting P. acnes and E. coli bacteria was IFED 1 (Nigrospora sp).